Reactualization of Indonesia- India Bilateral Relations1 - Yumitro, Gonda (Jurnal Hubungan Internasional, 2014)
After liberalized itâs economic policy in 1991, India emerges as a new emerging power in the world. By the year, itâs economic power supports the strengthening of itâs politics, military and cultures. Such condition invited Indonesia to be closer to India as what they had in previous time, since both countries also have consciousness on the emergence of Asian century after American and Europe have become weaker. Through this paper, I will position Indonesia and India mapping in International politics, particularly in term of their economic power. By this effort, it will be clear how important the reactualization of Indonesia-Indian bilateral relations in this globalized era. I also will analyze the prospect and obstacles of both countries relations.